2022
DOI: 10.3390/ani12192639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Rate and Environmental Enrichment on the Ontogeny of Pecking Behavior of Laying Hen Pullets Confined in Aviary Compartments during the First 4 Weeks of Life

Abstract: The objective of this study was to describe the ontogeny of the severe feather pecking (SFP), gentle feather pecking (GFP), aggressive pecking (AP), and enrichment pecking (EP) of non-beak-trimmed Lohmann Brown (LB)-pullets during the first 4 weeks of life (observation on 1st, 8th, 15th, 22nd, and 29th days of life) while they were kept within the compartments of a commercial rearing aviary (without access to a litter area). All chicks were placed into compartments of the middle tier of the aviary on the 1st d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Beyond these first 4 weeks of life, there is some evidence of improved plumage condition in pullets reared at lower stocking densities. Bestman et al (2009) found that risk of plumage damage increased at more than 18 pullets/m 2 by the end of the rearing period, while Schwarzer et al (2022) found that the risk of plumage damage increased across the range of 11.9-31.6 pullets/m 2 of animal densities by end of rear. Nicol et al (1999) found significantly more gentle feather pecking at 30 birds/m2 than at lower densities of 22, 14 or 6 birds/m 2 .…”
Section: Maximum Stocking Density For Pulletsmentioning
confidence: 99%
See 3 more Smart Citations
“…Beyond these first 4 weeks of life, there is some evidence of improved plumage condition in pullets reared at lower stocking densities. Bestman et al (2009) found that risk of plumage damage increased at more than 18 pullets/m 2 by the end of the rearing period, while Schwarzer et al (2022) found that the risk of plumage damage increased across the range of 11.9-31.6 pullets/m 2 of animal densities by end of rear. Nicol et al (1999) found significantly more gentle feather pecking at 30 birds/m2 than at lower densities of 22, 14 or 6 birds/m 2 .…”
Section: Maximum Stocking Density For Pulletsmentioning
confidence: 99%
“…(2009) found that risk of plumage damage increased at more than 18 pullets/m 2 by the end of the rearing period, while Schwarzer et al. (2022) found that the risk of plumage damage increased across the range of 11.9–31.6 pullets/m 2 of animal densities by end of rear. Nicol et al.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations